EU economic modelling system: Assessment of the European Institute of Innovation and Technology (EIT) investments in innovation and human capital - Olga Ivanova; D'Artis Kancs; Mark Thissen (Economics and Econometrics Research Institute (EERI), 2019)
This is the first study that attempts to assess the regional economic impacts of the European Institute of Innovation and Technology (EIT) investments in a spatially explicit macroeconomic model, which allows us to take into account all key direct, indirect and spatial spillover effects of EIT investments via inter-regional trade and investment linkages and a spatial diffusion of technology via an endogenously determined global knowledge frontier with endogenous growth engines driven by investments in knowledge and human capital. Our simulation results of highly detailed EIT expenditure data suggest that, besides sizable direct effects in those regions that receive the EIT investment support, there are also significant spatial spillover effects to other (non-supported) EU regions. Taking into account all key indirect and spatial spillover effects is a particular strength of the adopted spatial general equilibrium methodology; our results suggest that they are important indeed and need to be taken into account when assessing the impacts of EIT investment policies on regional economies.
Keywords: C68; D58; F12; R13; R30; 330; EIT; innovation; productivity; human capital; SCGE model; spatial spillovers